Advancements in Digital Broadcasting and Content Platforms - Erdem, Mevlüde Nur; Kus, ö.A. (IGI Global, 2025)
With the rise of high-speed internet, cloud computing, and AI-driven personalization, traditional broadcasting models evolve into on-demand systems catered to global audiences across multiple devices. Streaming services, digital radio, and interactive platforms now offer content variety and user control, reshaping viewer expectations and industry strategies. Further exploration into this digital transformation may enable real-time analytics, targeted advertising, and seamless content integration, fostering a more connected and responsive media landscape. Advancements in Digital Broadcasting and Content Platforms explores the theoretical, practical and conceptual aspects of digital broadcasting and content platforms. It examines the technological advances and transformations of emerging online platforms and user experiences. This book covers topics such as digital media, journalism, and mobile technology, and is a useful resource for media and communications professionals, business owners, computer engineers, academicians, researchers, and scientists. © 2026 by IGI Global Scientific Publishing. All rights reserved.